Técnica de pintura mixta para mejorar la creatividad en los niños de preparatoria de la escuela Rosa Josefina Burneo de Burneo de la ciudad de Loja, en el periodo 2019 – 2020 - Morocho Murillo, Sofia Maribel (2020)
The present thesis entitled: MIXED PAINTING TECHNIQUE TO IMPROVE CREATIVITY IN HIGH SCHOOL CHILDREN OF THE ROSA JOSEFINA BURNEO DE BURNEO SCHOOL IN THE CITY OF LOJA, IN THE PERIOD 2019 - 2020, was set as a general objective: To identify if the technique of Mixed paint helps enhance creativity. The methods used were scientific, analytical - synthetic, descriptive and statistical, among the techniques and instruments applied were: the survey of teachers and the Torrance Creativity Test, the selected sample was of 24 children between the ages of 5 and 6 years and 3 high school teachers. The results obtained in the initial diagnosis revealed that 67% of children were in low creativity, 25% in medium low creativity, 5% in high creativity and 3% in medium high creativity. Therefore, it was considered appropriate to develop the alternative proposal "Happy children" with the mixed painting technique, with activities related directly to drawing and painting. Once the intervention was finished, the post test was applied, presenting as results that 43% of children were ranked in high creativity, 38% in medium high creativity, 14% in medium low creativity and 5% in low creativity; demonstrating that the mixed painting technique favors creative development, for this reason teachers must apply it in their daily work, in order to contribute to the teaching process, allowing the child to participate and autonomous in their own learning.